Phenotypic Heterogeneity of the Mitochondrial DNA Variant m.13513 G > A - Finsterer, Josef (Journal of Pediatric Genetics, 2023)
The mitochondrial DNA (mtDNA) variant m.13513G > A is increasingly recognized as a cause of syndromic and nonsyndromic mitochondrial disorders (MIDs). This minireview aims a summarizing and discussing recent and previous findings about the phenotypic heterogeneity of this variant. A systematic literature review using the databases PubMed and Google Scholar by application of specific search terms was performed. As per the end of July 2021, at least 50 patients carrying the mtDNA variant m.13513G > A have been reported. Age ranged between 0 and 63 years, and of these patients, 28 were male and 22 were female. The phenotype was highly variable. The most common phenotypes were Leigh syndrome (LS; n = 25), mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS; n = 11), Leigh-like syndrome (n = 4), MELAS/LS (n = 3), progressive external ophthalmoplegia (n = 3), MELAS/Leber's hereditary optic neuropathy (LHON; n = 1), and LHON (n = 1). More rarely are nonsyndromic phenotypes. Heteroplasmy rates were highly variable ranging from 0 to 86% depending on the investigated tissue. The outcome was reported in only a few cases but was worse in patients with LS compared with those with MELAS. The variant m.13513G > A is responsible for syndromic or nonsyndromic MIDs. Syndromic MIDs in which this variant should be particularly considered include LS, MELAS, and LHON and their overlaps. Patients with suspected MID and maternal inheritance should undergo sequencing of the entire mtDNA not to miss rare mtDNA variants.
Keywords: mtDNA; Leigh's syndrome; MELAS; heteroplasmy; m.13513G > A